PELAKSANAAN PENYIDIKAN TERHADAP TINDAK PIDANA DESERSI DI SATUAN POLISI MILITER ANGKATAN UDARA (SATPOMAU) LANUD HALIM PERDANAKUSUMA - Mohamad Shokib Hasan (Fakultas Hukum Universitas Borobudur, 2024)
The issue of desertion often involves suspects who cannot be found so that Military Police action is needed to complete the investigation of desertion cases. This study discusses the investigation of desertion cases carried out at the Air Force Military Police Unit (Satpomau) Halim Perdanakusuma Air Force Base, the factors causing desertion among Indonesian National Army Air Force personnel, and the obstacles faced in the investigation of desertion cases at Satpomau Halim Perdanakusuma Air Force Base. The research methods used are normative and empirical legal research. The results of the study indicate that the investigation of the suspect was carried out in absentia because the suspect could not be called to provide information and could not be arrested because he was not found. Factors causing desertion include internal factors such as family problems, economic factors, the suspect's desire to desert, mental unpreparedness in carrying out military duties and responsibilities, faith and devotion to God Almighty, and lack of discipline. External factors include soldiers' lack of understanding of military regulations, accepting assignments that are not in accordance with expectations, and preferring to socialize in a free environment rather than obeying military regulations. The obstacles faced by the Military Police at Satpomau in investigating desertion cases include difficulty in summoning suspects, finding suspects, proving evidence only based on witness statements and attendance reports, examining suspects because they are not present, andinadequate facilities, infrastructure, and operational funds.